Benzyl isothiocyanate ameliorates cognitive function in mice of chronic temporal lobe epilepsy - Xiaoyu, Chang; Hongzhen, Zhou; Nan, Peng; Tengwei, Gao; Yanan, Gong; Yan, Guo; Haiyan, La; Li, Ma; Haiya, Wu; Yujun, Wen; Rui, Zhang (Frontiers in Neurology, 2024)
Temporal lobe epilepsy (TLE) is a prevalent refractory partial epilepsy seen in clinical practice, with most cases originating from the hippocampus and being characterized by impaired learning and memory. Oxidative stress plays a direct role in the development of epilepsy and neurodegeneration while promoting cognitive dysfunction. Previous research indicates that benzyl isothiocyanate (BITC) has antioxidative stress properties and contributes to neuroprotection. In this study, we aimed to investigate the neuroprotective effect of BITC on a lithium-pilocarpine-induced temporal lobe epileptic mice model. Our results demonstrate that BITC enhances cognitive function and motor ability in mice, as determined by Intellicage learning tests, Morris water maze, open field test, and step-down-type passive avoidance tests, respectively. In addition, body weight and brain-to-body ratio were calculated. Nissl staining, real-time quantitative PCR detection of nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase 1 (HO-1) and NAD(P)H dehydrogenase quinone 1(NQO1) were performed. Content of malondialdehyde (MDA) and activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and total antioxidant capacity (T-AOC) were determined. Epilepsy leads to the loss of neurons in the CA3 region, while BITC treatment plays a positive role in neuroprotection, especially in the cortex. In comparison to the control group, the EP group exhibited decreased transcription levels of HO-1 and NQO1, alongside reduced GSH-Px activity, while MDA content was elevated. Conversely, the BITC treatment group, when compared to the EP group, showed enhanced transcription levels of Nrf2, HO-1, and NQO1, along with increased GSH-Px activity, and a decrease in MDA content. In summary, our study provides evidence that BITC can improve cognitive impairments in pilocarpine-induced epileptic mice, demonstrating significant antioxidant effects and neuroprotective properties. This highlights its potential as a phytochemical for managing the sequelae of epilepsy.